Differential modulation of collybistin conformational dynamics by the closely related GTPases Cdc42 and TC10 - Imam, Nasir; Choudhury, Susobhan; Heinze, Katrin G.; Schindelin, Hermann (Frontiers in Synaptic Neuroscience, 2022)
Interneuronal synaptic transmission relies on the proper spatial organization of presynaptic neurotransmitter release and its reception on the postsynaptic side by cognate neurotransmitter receptors. Neurotransmitter receptors are incorporated into and arranged within the plasma membrane with the assistance of scaffolding and adaptor proteins. At inhibitory GABAergic postsynapses, collybistin, a neuronal adaptor protein, recruits the scaffolding protein gephyrin and interacts with various neuronal factors including cell adhesion proteins of the neuroligin family, the GABAA receptor 2-subunit and the closely related small GTPases Cdc42 and TC10 (RhoQ). Most collybistin splice variants harbor an N-terminal SH3 domain and exist in an autoinhibited/closed state. Cdc42 and TC10, despite sharing 67.4% amino acid sequence identity, interact differently with collybistin. Here, we delineate the molecular basis of the collybistin conformational activation induced by TC10 with the aid of recently developed collybistin FRET sensors. Time-resolved fluorescence-based FRET measurements reveal that TC10 binds to closed/inactive collybistin leading to relief of its autoinhibition, contrary to Cdc42, which only interacts with collybistin when forced into an open state by the introduction of mutations destabilizing the closed state of collybistin. Taken together, our data describe a TC10-driven signaling mechanism in which collybistin switches from its autoinhibited closed state to an open/active state.